Evaluating quality and reliability of final examination questions for MAT0144 using rasch model - Bahrom, Suhaila; Mat Yaacob, Siti Nubailah; Happas, A'fifah; Saidin, Nurhafizah (2022)
The construction of the final examination questions based on the proper guideline such as according to course learning outcomes (CLO) will help in measuring students’ abilities based on comprehensive cognitive skills. A well-constructed question on the final examination should be suitable for the intended level of knowledge. In this study, the results from final examination Statistics, MAT0144 taken by Biological Module students in Semester 3, 2021/2022 were analysed using the Rasch Model. It is a process of statistically examining both the test questions and the students’ answer to evaluate the quality and reliability of the test item and the examination paper as a whole. The items in the examination paper were studied and items that did not meet expectations were identified. The best test item discriminates between those students who perform well on the examination and those who do not. The items on the equal interval scale (logit) must keep their relative difficulty regardless the ability of the students that challenges the item. According to the analysis, the overall quality and reliability of the examination questions constructed were relatively good and calibrated with the students' learned ability and suitable for the intended students.